(3caGjI GdCUhds - (3GdNQGSGfj, GdCNhfO, eMeO cGXe, J (B1329 (3g`s
(3ChdgG (B:s
(3GdMeO ddg (B... (3aO QJHJg Ydi ebOeI hNGJeI CeG GdebOeI aaj HjGf GehQ ; GdChd (B: (3Cf ehVhY cd Yde hgh GdPj jLH hajg Yf YhGQV GdPGJjI Cj HdG hGSWI aj GdYQhV gh faS ehVhYGJ eSGFdg (B...s
(3BNQgG (B:s
... (3heHjfG dOi GdBNQ deYQaJg hYOe GdJUGOe HfXQg adG jgefG GdJYQV dehGQO GdNdGa hGdcdGe hGdfaV hGdEHQGe aj GdebGe hYdi Gddg GdJhcd hHg GdGYJUGes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7\11s
(3GdPQjYI (B18 - 58 (810)s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs